Proximal Jejunal Diverticle: Cause of Upper Gastrointestinal Bleeding - Andree Kurniawan; Marcellus Simadibrata; Arshita Auliana; Armen Armen; Achmad Fauzi (The Indonesian Society for Digestive Endoscopy, 2012)
Five percents of patient presenting with gastrointestinal (GI) bleeding, the etiology of bleeding could not be found by upper endoscopy and colonoscopy. Almost 75% of which, the abnormality is detected in small bowel. One of the etiologies in small bowel bleeding is jejunal diverticle. In this paper, we reported a female, 38 years old, came with upper GI bleeding since one month ago. She had undergone several diagnostic procedures, such as abdominal ultrasound, abdominal computed tomography scan (CT-scan), upper and lower endoscopy, but there were no conclusion to explain the cause of bleeding. However, barium follow through examination found a diverticle, pouch-like shape, at jejunal proximal projection. Then, she underwent surgical treatment. Small intestine bleeding is best investigated by capsule endoscopy and double balloon enteroscopy. However, in limited conditions, small bowel follow through can be used to screen the source of bleeding in small intestine. The specific diagnosis of small intestine diverticle is possible by radiologic contrast study using various form of barium. Small bowel diverticle does not require surgical treatment, unless refractory symptoms or complications occur. Jejunal diverticle is one of sources in small intestinal bleeding. Small bowel follow through can still be used to diagnose jejunal diverticle. Keywords: diverticle, proximal jejunal, upper gastrointestinal bleeding, barium follow through